Inhibition of siglec-1 by lentivirus mediated small interfering RNA attenuates atherogenesis in apoE-deficient mice - Xiong, Yi-Song (Clinical immunology (Orlando, Fla.), 2017)
Copyright © 2016 Elsevier Inc. All rights reserved.